Autism spectrum disorder (ASD): Lines of care and public policies in Brazil - Correa , Kelly de Souza; Barbosa, Roberta Ribeiro Batista; Oliveira, Fernando Rocha (Seven Editora, 2023)
Over the years, public policies aimed at Autism Spectrum Disorder (ASD) have evolved in Brazil. Despite this, we still face challenges, such as expanding access to specialized services and raising societal awareness of ASD. It is important that the diagnosis is made early by a multidisciplinary team, so that appropriate treatment can be started as early as possible. Treatment involves several interventions and should be personalized. In addition, it is essential that public policies ensure access to quality diagnosis and treatment for all. The purpose of this chapter is to analyze the Ministry of Health guidelines for the treatment of Autism Spectrum Disorder and to discuss possible long-term consequences. Challenges related to the diagnosis and treatment of autism in the context of the Unified Health System are also addressed. This is a narrative literature review, which aims to understand the development of Autism Spectrum Disorder (ASD), its Lines of Care and Public Policies in Brazil, through the analysis of the scientific production available in the databases Scientific Electronic Library Online (Scielo), National Library of Medicine (PubMed), books and other informative media. Autism Spectrum Disorder (ASD) in Brazil still faces challenges, such as a lack of trained professionals and unequal resources. To ensure adequate and quality care, it is necessary to invest in training and training of professionals, awareness of families and joint work between government, civil society and families, making it possible to build a more inclusive and welcoming society for people with ASD. DOI:https://doi.org/10.56238/chaandieducasc-009